Peningkatan Kemampuan Memahami Haji dan Umroh di Kelas IXA Siswa SMP Negeri 2 Panti Kabupaten Jember dengan Teknik Jigsaw Semester II Tahun Pelajaran 2016/2017 - Mariyatul Qibtiyah (FKIP Universitas Islam Jember, 2017)
This study aims to improve students’ learning achievement on Hajj and Umrah Basic Competence using Jigsaw technique at Junior High school level. The research participants are 30 ninth grade students at SMP Negeri 2 Panti. Action research with two cycles is implemented as the research design of this study. The results show the students’ average scores respectively from the pre cycle, cycle I, and cycle II are 70,67%, 76,66%, and 84,16%. The result of observation yields that students’ activeness increase respectively from cycle I to cycle II ranging from 75% to 90%. Teacher activities also increase from 81% to 95%. The result of interview admits that most of the students are motivated and interested in learning using Jigsaw technique. From the results above it can be inferred that Jigsaw learning method can improve both students’ learning achievement and motivation.Keywords: using Jigsaw, Hajj and Umrah